The response of an autonomous underwater telescope to high energy neutrinos for the observation of Gamma-ray bursts (GRBs) - Balasi, K.; Markou, C.; Tzamarioudaki, K.; Rapidis, P.; Drakopoulou, E.; Pikounis, K.; Begatelas, C. (HNPS Advances in Nuclear Physics, 2019)
The response of an underwater neutrino detector is discussed for investigating its performance to the detection of muons and high energy neutrinos. The afformentioned telescope consists of an autonomous battery operated detector string to a central 4-floor tower. In this aim, we utilised a fast detector simulation program, SIRENE, to simulate the hits from Cherenkov photons at ultra high energies (as high as 1020 eV). In order to optimize the detector, analytical studies for different configurations and characteristics of the photo-multiplier tubes inside the optical modules of the telescope was also examined.